Exploring the dynamic impact of biomass energy, deforestation, fossil fuels and green technology on greenhouse gas emissions in China - Chen, Yuan; Arshad, Rimsha (Frontiers in Environmental Science, 2026)
China faces the dual challenge of sustaining economic growth while reducing greenhouse gas (GHG) emissions, yet the combined effects of energy structure, technological innovation, and land-use policies remain underexplored. This study examines the long- and short-run drivers of GHG emissions across Chinese provinces from 2000 to 2022 using second-generation panel estimators that address cross-sectional dependence and slope heterogeneity (CS-ARDL, AMG, CCEMG). A unique contribution of this work is the joint inclusion of biomass energy use, fossil energy consumption, energy intensity, green technology innovation, and deforestation dynamics within a unified empirical framework. The results show that fossil fuel use and energy intensity significantly accelerate emissions, while innovation and afforestation policies help mitigate environmental pressures. Biomass energy increases emissions due to continued reliance on traditional rural combustion practices. These findings provide new empirical evidence to guide China’s transition toward clean energy, innovation-led growth, and strengthened forest-based carbon sinks in support of long-term decarbonization strategies.